Study on Associated Risk Factors of Hypertension at Sipaghat of Sindhupalchowk District, Nepal - Manandhar, Naresh (Nepalese Journal of Statistics, 2017)
Background: Hypertension is a progressive cardiovascular syndrome arising from complex and interrelated etiologies. Males have slightly higher prevalence than female in most of countries of Southeast-Asian region. Objective: The objective of study is to find out prevalence and the risk factors of hypertension at Sipaghat, Sindhulchowk, Nepal. Materials and Methods: A cross-sectional study was conducted at Sipaghat of Sindhupalchowk district in May 2016 and 260 persons were selected randomly. Results: The prevalence of hypertension was higher in male (25.4%) than female (17.4%). Mean age of study population was 42.08 years with standard deviation, 15.95 years. Variables namely age group, smoking, alcohol consumption and family history of hypertension were found to be significant at 5 percent level of significance. Alcohol consumption and smokers have more than two times higher chance of getting hypertension compared to alcohol non-consumer and nonsmoker with 95% confidence intervals were 1.08-4.80 and 1.21-6.10, respectively. Persons with family history of hypertension have 3.8 times more chance of getting hypertension compared to no family history of hypertension with 1.89-7.61 of 95% confidence interval. Conclusion: Lifestyle modification reduces blood pressure which prevents or delays the incidence of hypertension. Hypertension can be controlled and prevented by modifying the lifestyle. People should be advised to avoid modifiable risk factors of hypertension like smoking, consumption of alcohol and physical inactivity through health education programs. Nepalese Journal of Statistics, 2017, Vol. 1, 73-82